AS: a novel sentimental analysis approach - Shabaz, Mohammad; Kumar, Ashok (International Journal of Engineering and Technology, 2018)
It is interesting to know about the things which are unknown. Just like the emotions, feelings, opinion, sentiments. The term sentimental analysis relates to all these above discussed terms. The extraction of opinion or sentiments from the data through the analysis is called sentimental analysis. There are different kinds of approaches but deal with extraction of sentiments. But none of the approach gives the accurate results. Since sentiments are directly related to human behaviour and human behaviour is not algorithmic. In this paper we have designed another novel approach named as AS analysis. AS analysis is one of new design to overcome the limitation of positive and negative word comparison with input text after tokenization. In this approach we have designed a new formula to find the sentiments count that ranges from -1 to +1 where negative values denotes the negative sentiments and positive values denotes the positive sentiments and 0 denotes the neutral sentiments. By this approach we conclude that the results we have obtained are near to accurate since there is no measure of accuracy it varies from individual to individual, so performing sentimental analysis always gives approximate results.Â Â